Bullying in Undergraduate Medical Education of Bangladesh : Situation Analysis (Bangladesh Journal of Medical Education, 2025)
This was descriptive type of cross sectional study. Both quantitative and qualitative approaches were applied to explore current situation of bullying among undergraduate medical students of Bangladesh. Study was designed to find out categories of bullying occurred, persons involved in bullying, factors contributing for the occurrence of bullying, effects of bullying on the students and steps to be taken against the bullying. The study was carried out in eight (five government and three non government) medical colleges in Bangladesh over a period from July 2023 to June 2024. Undergraduate medical students and teachers of medical colleges were the study population. Sample size was 632 for administering questionnaire to the students, 16 for focus group discussion to the students and 16 for in-depth interview of the teachers. Convenience sampling technique was adopted to enroll the respondents and to select medical colleges. Data was collected from those who were present at the time of data collection and respondents willing to participate in the study as respondents. One self administered semi structured questionnaire was used for data collection. A schedule for focus group discussion was used to collect data from two groups of undergraduate medical students and a schedule for in-depth interview was used to collect data from the teachers of medical colleges. Prior informed consent from the respondents was taken. Study revealed that verbal bullying was most common type of bullying. Other types of bullying were physical, political, economical and cyber bullying. According to gender, male, students are more involved in bullying than female students. According to residence status, majority of the students involved in bullying behavior were residing in the hostel. According to economical status, students belongs to middle class family were involved more in bullying activities. Senior students were involved more in bullying, other persons were peer students, teachers, staff of medical college and hospitals administrators of medical colleges and hospitals, was also involved to some extent. Study also revealed that environment of college campus and hostels play important roles in occurrence of bullying. Other factors involved in bullying are weak administration, student politics, teachers politics and lack of monitoring by the authority. Anxiety, depression, academic regression were common effects of bullying on the students. Other effects were physical illness, leave hostel, leave medical colleges and suicidal tendency. Several steps to be taken to prevent bullying in medical colleges. Most important steps are staying of super in the hostel, taking appropriate action by local authority, and counseling and motivation to the students, opportunity of the students to inform local and higher authority and action taken to prevent recurrence of bullying. Study recommend supporting undergraduate medical students by preventing bullying. This could be achieved by launching educational program, establishing students support system, increasing cultural program among medical students, developing awareness among medical students, teachers and ensuring punishment of liable individual as per policy.BJME, Volume-16, Issue-01, January 2025: 2-14